Equity Crowdfunding in Indonesia: Complying with Regulations and Legal Consequences for Investors: Equity Crowdfunding di Indonesia: Mematuhi Peraturan dan Konsekuensi Hukum bagi Investor - Ningrum, Hesti; Multazam, M Tanzil (Universitas Muhammadiyah Sidoarjo, 2022)
This research aims to understand the equity crowdfunding scheme that has been adjusted to the existing regulations and the legal consequences for investors who invest in unregistered equity crowdfunding in Indonesia. Normative research method with the approach of applying the law was used, and primary and secondary legal materials were utilized. The findings show that there is an equity crowdfunding scheme that complies with the applicable regulations. As for the legal consequences, investors who invest in unregistered equity crowdfunding in Indonesia may face legal sanctions. The research contributes to the understanding of equity crowdfunding in Indonesia and provides insights for regulators, investors, and startups/UMKM seeking alternative funding sources. Highlights: Equity crowdfunding scheme in Indonesia complying with regulations. Legal consequences for investors investing in unregistered equity crowdfunding. Contribution to understanding equity crowdfunding and providing insights for stakeholders.